Unravelling the fuzzy effect of economic, social and environmental sustainability on the corporate reputation of public-sector organizations: a case study of Pakistan - Irfan, Muhammad; Hassan, Mazlan; Hassan, Nasruddin (MDPI, 2018)
The purpose of this study is to present and to validate a research model that includes economic sustainability, social sustainability, environmental sustainability and corporate reputation in the context of public-sector organizations in Pakistan. The methodological approach is survey-based, using partial least squares structural equation modelling (PLS-SEM) to assess the research model. The proposed hypotheses were tested based on a sample of 425 respondents from public-sector organizations in Pakistan. The findings of the study indicate that there is a positive relationship between economic sustainability, social sustainability, environmental sustainability and corporate reputation. Therefore, it is inferred from the results that different aspects of sustainability can create and enhance the reputation of public-sector organizations.